Postoperative minimal overcorrection in the surgical management of intermittent exotropia. Issue 7 (4th May 2013) - Cho, Yoonae A; Kim, Seung-Hyun
Abstract : Purpose: To investigate the effect of initial postoperative minimal overcorrection on the result of the surgical management of intermittent exotropia based on long-term follow-up results. Methods: 111 patients who underwent surgery for intermittent exotropia and were followed up for at least 5 years after surgery were retrospectively reviewed. The outcome was judged to be successful when there was 10 prism dioptres (PD) or less of exodeviation and less than 5 PD of esodeviation without any reoperation at the final follow-up visit. We evaluated the success, recurrence, overcorrection rate and the duration of diplopia according to their initial deviation. Results: We divided patients into four groups based on their initial deviation: orthophoria or undercorrection (Ortho group, 31 patients), minimally overcorrected at 5 PD or less (MO group, 20 patients), usually overcorrected between 6 PD and 10 PD (UO group, 35 patients), and highly overcorrected at more than 10 PD (HO group, 25 patients). The success rate was 43–60% between the four groups (p=0.52). The recurrence rate was 28–57% (p=0.105), but post hoc analysis showed borderline p values between the Ortho and HO group (p=0.024). No overcorrection was noted in the Ortho and MO groups (p=0.04). The duration of diplopia was 0–2.5 weeks, showing statistically significant difference among groups (p<0.001). Conclusions: The amount of initial postoperative overcorrection may not predict the long-term success rate. However, the MO group showed a lower recurrence rate than the Ortho group and also showed no overcorrection and a shorter duration of postoperative diplopia than the UO and HO groups.